SOCIAL AND PEDAGOGICAL CONDITIONS OF INTEGRATION OF CHILDREN WITH SPECIAL EDUCATIONAL NEEDS IN THE MODERN INFORMATION SOCIETY - Dudka, Olga; Dzhoholyk, Oksana (Mountain School of Ukrainian Carpaty, 2018)
In the article, the main features of social and pedagogical integration of students with special educational needs into the modern information society are considered based on the implementation of inclusive learning. The importance of developing digital skills of children with special educational needs substantiated. Including students with special education needs into the general education space is one of important ways of humanization of the national education system. Due to the implementing inclusive learning in educational institutions of Ukraine the basic right of a child to education is satisfied. The main task of inclusive learning is to provide a welcoming experience for all students to get the quality education. Inclusive learning takes into account individual characteristics of students with special education needs and so, facilitates their adaptation in a school. One of the key tasks of the modern education is creating inclusive learning environment in which teachers and students are open to the collaboration and communication. The important social problem is to remove barriers that impede the full life of persons with special needs. Modern digital technologies adopted for different needs of users became an integral part of life of persons with special needs. Compensatory property of new technologies allows students with special needs actively to participate in the educational process. The process of teaching children with special educational needs requires development of so many new methodological materials which help such students integrate into the modern information society. Through the implementation of digital technologies in the learning process and in the inclusive learning, in particular, children with special educational needs can receive a variety of educational materials in an accessible format, more effectively master new knowledge and demonstrate their educational achievement. Therefore, using modern digital technologies in the inclusive learning provides effective way for integration of children with special needs into the educational process and the information society.